Diabetes education and health insurance: How they affect the quality of care provided to peoplewith type 1 diabetes in Latin America. Data from the International Diabetes Mellitus Practices Study (IDMPS) - Gagliardino, Juan Jose (2019)
Aims: This study aimed to evaluate the impact of diabetes education and access to healthcare coverage on disease management and outcomes in Latin America. Methods: Data were obtained from a sub-analysis of 2693 patients with type 1 diabetes mellitus recruited from 9 Latin American countries as part of the International Diabetes Mellitus Practices Study (IDMPS), a multinational, observational survey of diabetes treatment in developing regions. Results: Results from the Latin American cohort show that only 25% of participants met HbA1c target value (< 7% [53 mmol/mol]). Attainment of this target was significantly higher among participants who had received diabetes education than those who hadn´t (28% vs. 19%, p < 0.001), and among those who practiced self-management (27% vs. 21% no self-management, p = 0.001). Multivariate analysis showed that participants who had received diabetes education were more likely to manage their diabetes (OR: 1.65 [95% CI: 1.24, 2.19]; p = 0.001), and to attain HbA1c target values (OR: 1.48 [95% CI: 1.14, 1.93]; p = 0.003). Conclusions: Given the association between uncontrolled diabetes and long-term complications, health authorities and care providers should increase efforts to ensure widespread healthcare coverage and access to self-management education to reduce the socioeconomic and humanistic burden of type 1 diabetes.